Minding the gap: changes in life expectancy in the Baltic States compared with Finland. Issue 11 (11th April 2012) - Karanikolos, Marina; Leon, David A; Smith, Peter C; McKee, Martin
Abstract : Background: In the 20 years since the three Baltic States, Estonia, Latvia and Lithuania, have been independent, they have converged progressively with a Western neighbours, politically economically and socially. In contrast, the health gap has widened. Methods: Trends in life expectancy in the three Baltic States were compared with Finland and were decomposed by age for the years 1994, 1999, 2004 and 2009 and by cause of death for year 2009. 1994 was when life expectancy fell to its lowest level since the three countries regained independence. Results: From the mid-1980s to the mid-1990s, the gap in life expectancy between the three Baltic States and Finland widened, especially for men. It then narrowed progressively, except Lithuania where it widened again after 1999. Decomposition by age reveals that the narrowing gap has been driven largely by reduced mortality at working ages, partly counteracted by a relative failure to improve at older ages, especially in Lithuania. Decomposition by cause of death identifies diseases of the circulatory system as the largest contributor to the gap, with the contribution largest at older ages. However, cancer deaths, especially among men, are also important as are deaths from external causes among younger men. Conclusions: Although the gaps in life expectancy between the Baltic States and Finland have reduced, improvements, especially in Latvia and Lithuania, have been fragile. There is a clear need to act on the leading causes of the persisting gap with Finland, in particular through action on hazardous drinking and other risk factors for cardiovascular disease.